Long non-coding RNA HAGLR: The potential biomarker plays an important role in idiopathic pulmonary fibrosis - Hu, Lijuan; Liu, Ruoyu; Han, Siqi; Zhang, Ruyue; Zhou, Yun; Cao, Yongtong (Gene, 2025)
•This is the first study to investigate the role of lncRNA HAGLR in IPF.•HAGLR can distinguish IPF from other pulmonary diseases.•HAGLR can influence the fibrosis process at the cellular level. Idiopathic pulmonary fibrosis (IPF), the most common interstitial lung disease, has a severe prognosis, and its diagnosis is difficult. Long non-coding RNAs (lncRNAs) play crucial roles in the mechanism of IPF and exhibit great potential as biomarkers. Past research found that HOXD antisense growth-associated lncRNA (HAGLR) was elevated in IPF. Therefore, this study assessed the diagnostic utility and function of HAGLR in IPF. HAGLR expression was screened in the Gene Expression Omnibus datasets. Then, the serum specimens and clinical information of 66 patients with IPF, 93 patients with interstitial lung disease (ILD) without IPF, 61 patients with pneumonia, and 58 healthy controls were simultaneously collected. HAGLR expression was tested in all subjects and analyzed using receiver operating characteristic curves to verify the clinical utility of HAGLR. Then, the effects of HAGLR inhibition on fibrosis-related gene and protein expression in a cell model of fibrosis were investigated by quantitative reverse transcription-polymerase chain reaction and western blotting. HAGLR expression was higher in patients with IPF than in healthy controls, patients with ILD without IPF, and patients with pneumonia. The ROC curve analysis illustrated that HAGLR can distinguish patients with IPF from healthy controls. A model combining clinical items (including age, gender, routine blood test, tumor biomarkers, and cytokines), with HAGLR displayed good clinical value, with an are under the curve of 0.994, sensitivity of 100.0% and specificity of 91.4%. Upon HAGLR inhibition, fibrosis proteins were downregulated. HAGLR has utility in the auxiliary diagnosis of IPF, as it can differentiate IPF from other conditions. HAGLR inhibition could alleviate fibrosis at the cellular level.